Finite Element Analysis of Structures Using C1-Continuous Cubic B-Splines or Equivalent Hermite Elements. (13th November 2014) - Provatidis, Christopher
Abstract : We compare contemporary practices of global approximation using cubic B-splines in conjunction with double multiplicity of inner knots (C 1 -continuous) with older ideas of utilizing local Hermite interpolation of third degree. The study is conducted within the context of the Galerkin-Ritz formulation, which forms the background of the finite element structural analysis. Numerical results, concerning static and eigenvalue analysis of rectangular elastic structures in plane stress conditions, show that both interpolations lead to identical results, a finding that supports the view that they are mathematically equivalent.